THE EFFECT OF PROFIT-SHARING FINANCING, SALE AND PURCHASE FINANCING AND INTELLECTUAL CAPITAL ON FINANCIAL PERFORMANCE AT ISLAMIC COMMERCIAL BANKS IN 2017-2021 - Serly Nufia Juliana; Rusdi (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2023)
This study analyzes the effects of Profit-Sharing Financing, Sale-purchase Financing, and Intellectual Capital on Financial Performance. Profit Sharing Financing in this study is calculated using the total of Musharakah financing and Mudharabah financing, while Sale-purchase Financing is calculated based on the total of sale-purchase financing. Intellectual Capital is proxied using VACA, and Financial Performance is proxied using ROE. The population in this study consists of all Islamic banks registered with the Financial Services Authority (OJK) in Indonesia for the period 2016-2020. The technique employed is a purposive sampling technique with four specific criteria as considerations, resulting in a sample of 8 companies with a five-year period, yielding a total of 40 observational data points. The data analysis employed in this study utilizes panel data regression with the assistance of EViews 9. The partial findings of this study indicate that only the variable of sale-purchase financing has a significant effect on financial performance, while the variables of profit-sharing financing and intellectual capital do not exhibit an effect on financial performance.